2009
DOI: 10.1021/ic900853e
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to the Hydrazone Functionalized PdGeS Cluster [{RNGe(μ-S)3}4Pd6] from the Thiogermanate Anion [{RNGe}2(μ-S)2S2]2−

Abstract: Compound 2•MeOH Pd1-S5 2.320(3) Pd6-S11 2.363(3) Pd1-S1 2.322(3) Ge1-C41 1.987(10) Pd1-S6 2.382(3) Ge1-N1 2.228(9) Pd1-S11 2.393(3) Ge1-S5 2.240(3) Pd2-S2 2.328(3) Ge1-S9 2.245(3) Pd2-S6 2.338(3) Ge1-S1 2.379(3) Pd2-S7 2.339(3) Ge2-C43 1.987(11) Pd2-S3 2.349(3) Ge2-S11 2.231(3) Pd3-S4 2.309(3) Ge2-S6 2.271(3) Pd3-S8 2.325(3) Ge2-N3 2.274(10) Pd3-S7 2.390(3) Ge2-S2 2.354(3) Pd3-S12 2.392(3 Ge3-C42 1.991(12) Pd4-S10 2.363(3) Ge3-S12 2.247(3) Pd4-S5 2.377(3) Ge3-S7 2.260(3) Pd4-S9 2.381(3) Ge3-N5 2.280(10) Pd4-S8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…those with longer bonds to the T atom, are occupied by the other bridging sulfur atom (S1a) and one nitrogen atom of the thiosemicarbazone ligand (N1) in a slightly declined fashion (µ‐S i –T–N = 160.80(14)–168.69(9)°). The intramolecular distances in 1 are in agreement with other reported hydrazone functionalized thiogermanate complexes, like (NH 3 NH 2 ) 2 [{R N Ge} 2 (µ‐S) 2 S 2 ] (R N = CMe 2 CH 2 CMeNNH 2 ),7a and with other reported Ge–(µ‐S) bond lenghts 4b,14. The structural parameters of complexes 2 – 4 also correlate well with values found in the literature 6a,9,15…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…those with longer bonds to the T atom, are occupied by the other bridging sulfur atom (S1a) and one nitrogen atom of the thiosemicarbazone ligand (N1) in a slightly declined fashion (µ‐S i –T–N = 160.80(14)–168.69(9)°). The intramolecular distances in 1 are in agreement with other reported hydrazone functionalized thiogermanate complexes, like (NH 3 NH 2 ) 2 [{R N Ge} 2 (µ‐S) 2 S 2 ] (R N = CMe 2 CH 2 CMeNNH 2 ),7a and with other reported Ge–(µ‐S) bond lenghts 4b,14. The structural parameters of complexes 2 – 4 also correlate well with values found in the literature 6a,9,15…”
Section: Resultssupporting
confidence: 90%
“…Here the original [Ge 4 S 6 ] adamantane complex is retained while the ligands undergo the condensation into the hydrazones 6b. The reactions presented in this work resemble more the reaction pathway that was observed upon reaction of [(R 1 Ge) 4 S 6 ] with hydrazine hydrate, which resulted in the formation of a hydrazonium salt of a hydrazone functionalized, smaller thiogermanate complex, namely (NH 3 NH 2 ) 2 [{R N Ge} 2 (µ‐S) 2 S 2 ] (R N = CMe 2 CH 2 CMeNNH 2 ) is formed under cleavage of the [Ge 4 S 6 ] precursor cage 7a…”
Section: Resultsmentioning
confidence: 99%
“…Network compounds featuring group 14 elements with sulfur or selenium linkers exhibit intriguing chemical and physical properties as well as applications . One of the common protocols to access thiostannates is the solvothermal route that utilizes different amines as structure‐directing agents such as (C 2 H 10 N 2 )(C 2 H 9 N 2 ) 2 [Sn 2 S 6 ], R 2 Sn 3 S 7 [R = tetramethylammonium (TMA), [SnS 2 · en] (en = ethylene diamine), (C 6 H 20 N 4 ) 2 [SnS 2 ] · 2H 2 O, diazabicyclooctane (DABCO), ammonium/tetraethylammonium (ATEA), tetraethylammonium (TEA)], R′ 2 Sn 4 S 9 [R′ = tetrapropylammonium (TPA), tetrabutylammonium (TBA)], and (enH) 4 [Sn 2 S 6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] It has been shown that it is possible to control the assembly of discrete organotin-sulfide moieties by the judicious selection of suitable bifunctional organic spacer groups. [11] However, investigations of the rearrangement of the inorganic core itself have not been implied so far, except for those on the unique formation of noradamantane-type structures [(RGe) 4 E 5 ].…”
Section: Introductionmentioning
confidence: 99%